TRANSIENT ELASTOGRAPHY (TE) IS A USEFUL TOOL FOR ASSESSING THE RESPONSE OF LIVER IRON CHELATION IN SICKLE CELL DISEASE PATIENTS - SOPHIA DELICOU (Mediterranean Journal of Hematology and Infectious Diseases)
Sickle cell disease patients often need regular blood transfusions to improve both the quality of life and survival from the veno-occlusive complications of the disease. Deferasirox, a convenient long acting oral agent, has recently been introduced in clinical practice with promising efficacy.